Zoonotic diseases transmitted from the camels - Khalafalla, Abdelmalik Ibrahim (Frontiers in Veterinary Science, 2023)
Background: Zoonotic diseases, infections transmitted naturally from animals to humans, pose a significant public health challenge worldwide. After MERS-CoV was discovered, interest in camels was raised as potential intermediate hosts for zoonotic viruses. Most published review studies pay little attention to case reports or zoonotic epidemics where there is epidemiological proof of transmission from camels to humans. Accordingly, any pathogen found in camels known to cause zoonotic disease in other animals or humans is reported. Methods: Here, zoonotic diseases linked to camels are reviewed in the literature, focusing on those with epidemiological or molecular evidence of spreading from camels to humans. This review examines the risks posed by camel diseases to human health, emphasizing the need for knowledge and awareness in mitigating these risks. Results: A search of the literature revealed that eight (36.4%) of the 22 investigations that offered convincing evidence of camel-to-human transmission involved MERS, five (22.7%) Brucellosis, four (18.2%) plague caused by Yersinia pestis, three (13.6%) camelpox, one (4.5%) hepatitis E, and one (4.5%) anthrax. The reporting of these zoonotic diseases has been steadily increasing, with the most recent period, from 2010 to the present, accounting for 59% of the reports. Additionally, camels have been associated with several other zoonotic diseases, including toxoplasmosis, Rift Valley fever, TB, Crimean-Congo hemorrhagic fever, and Q fever, despite having no evidence of a transmission event. Transmission of human zoonotic diseases primarily occurs through camel milk, meat, and direct or indirect contact with camels. The above-mentioned diseases were discussed to determine risks to human health.MERS, Brucellosis, plague caused by Yersinia pestis, camelpox, hepatitis E, and anthrax are the main zoonotic diseases associated with human disease events or outbreaks. Transmission to humans primarily occurs through camel milk, meat, and direct contact with camels. There is a need for comprehensive surveillance, preventive measures, and public health interventions based on a onehealth approach to mitigate the risks of zoonotic infections linked to camels.